Eficiencia y justicia en la empresa sanitaria - Conill Sancho, Jesús (Veritas, 2006)
The author analyzes the notions of efficiency/effectiveness, justice/equality and efficiency/justice in the administration of sanitary resources. In this sense, he shows the necessity to recognize that the incorporation of economic rationality in the sanitary field constitutes a concern of the first order in the field of the bioethics.